Tumor grading of soft tissue sarcomas using MRI-based radiomics - Peeken, Jan C.; Spraker, Matthew B.; Knebel, Carolin; Dapper, Hendrik; Pfeiffer, Daniela; Devecka, Michal; Thamer, Ahmed; Shouman, Mohamed A.; Ott, Armin; Von Eisenhart-Rothe, Ruediger; Nuesslin, Fridtjof; Mayr, Nina A.; et al. (EBioMedicine, 2019)
Background: Treatment decisions for multimodal therapy in soft tissue sarcoma (STS) patients greatly depend on the differentiation between low-grade and high-grade tumors. We developed MRI-based radiomics grading models for the differentiation between low-grade (G1) and high-grade (G2/G3) STS. Methods: The study was registered at ClinicalTrials.gov (number NCT03798795). Contrast-enhanced T1-weighted fat saturated (T1FSGd), fat-saturated T2-weighted (T2FS) MRI sequences, and tumor grading following the French Federation of Cancer Centers Sarcoma Group obtained from pre-therapeutic biopsies were gathered from two independent retrospective patient cohorts. Volumes of interest were manually segmented. After preprocessing, 1394 radiomics features were extracted from each sequence. Features unstable in 21 independent multiple-segmentations were excluded. Least absolute shrinkage and selection operator models were developed using nested cross-validation on a training patient cohort (122 patients). The influence of ComBatHarmonization was assessed for correction of batch effects. Findings: Three radiomic models based on T2FS, T1FSGd and a combined model achieved predictive performances with an area under the receiver operator characteristic curve (AUC) of 0.78, 0.69, and 0.76 on the independent validation set (103 patients), respectively. The T2FS-based model showed the best reproducibility. The radiomics model involving T1FSGd-based features achieved significant patient stratification. Combining the T2FS radiomic model into a nomogram with clinical staging improved prognostic performance and the clinical net benefit above clinical staging alone. Interpretation: MRI-based radiomics tumor grading models effectively classify low-grade and high-grade soft tissue sarcomas. Fund: The authors received support by the medical faculty of the Technical University of Munich and the German Cancer Consortium.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Biomarker; MRI; Radiomics; Risk stratification; Soft tissue sarcoma; Tumor grading